If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4.3(y + 6) = 30 Reorder the terms: 4.3(6 + y) = 30 (6 * 4.3 + y * 4.3) = 30 (25.8 + 4.3y) = 30 Solving 25.8 + 4.3y = 30 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-25.8' to each side of the equation. 25.8 + -25.8 + 4.3y = 30 + -25.8 Combine like terms: 25.8 + -25.8 = 0.0 0.0 + 4.3y = 30 + -25.8 4.3y = 30 + -25.8 Combine like terms: 30 + -25.8 = 4.2 4.3y = 4.2 Divide each side by '4.3'. y = 0.976744186 Simplifying y = 0.976744186
| [2n+5]=11 | | 2(x+7)=10x-10 | | 12+(-57)= | | -3x-2=-4x-8 | | -5x+9=-6x-3 | | 12-7j=-2 | | 12y-3y=7 | | 2(-1+x/3)=12 | | m^2+2m-1m-5m-10+1=0 | | 5+2j=-13 | | 3(x+4)=4x-5 | | -7a+11b= | | 15=m+-9 | | 5n^2+8n-36=0 | | p^2-2px+x^2=y^2 | | 4(x+3)=14 | | t*6-5=15 | | 20/35*45/4= | | 3(4x+6y)=15 | | a*4+4=14 | | M^2+2m-1m-5m-10-1=0 | | x(x+12)=32 | | 7-0.03x=1.72+1.75 | | [4+2]=6 | | (n+8m)(n+3m)-(n+m)(n-4m)=7x | | 5x-2x+6=x+18 | | 3(4-3c)=c-6 | | 3p+5=2p+15 | | 8*x=72 | | -7(f+1)-6=-41f+55 | | x(x-3)(x+3)=0 | | .4y=9 |